Phase singularity point tracking for the identification of typical and atypical flutter patients: A clinical-computational study. (January 2019) - Liberos, A.; Rodrigo, M.; Hernandez-Romero, I.; Quesada, A.; Fernandez-Aviles, F.; Atienza, F.; Climent, A.M.; Guillem, M.S.
Abstract: Atrial Flutter (AFL) termination by ablating the path responsible for the arrhythmia maintenance is an extended practice. However, the difficulty associated with the identification of the circuit in the case of atypical AFL motivates the development of diagnostic techniques. We propose body surface phase map analysis as a noninvasive tool to identify AFL circuits. Sixty seven lead body surface recordings were acquired in 9 patients during AFL (i.e. 3 typical, 6 atypical). Computed body surface phase maps from simulations of 5 reentrant behaviors in a realistic atrial structure were also used. Surface representation of the macro-reentrant activity was analyzed by tracking the singularity points (SPs) in surface phase maps obtained from band-pass filtered body surface potential maps. Spatial distribution of SPs showed significant differences between typical and atypical AFL. Whereas for typical AFL patients 70.78 ± 16.17% of the maps presented two SPs simultaneously in the areas defined around the midaxialliary lines, this condition was only satisfied in 5.15 ± 10.99% (p < 0.05) maps corresponding to atypical AFL patients. Simulations confirmed these results. Surface phase maps highlights the reentrant mechanism maintaining the arrhythmia and appear as a promising tool for the noninvasive characterization of the circuit maintaining AFL. The potential of the technique as a diagnosis tool needs to be evaluated in larger populations and, if it is confirmed, may help in planning ablation procedures. Highlights: Body surface phase mapping is presented as a potential atrial flutter diagnosis tool. Reentrant activity around a single obstacle results in two singularity points in the torso. Typical atrial flutter patients present singularity points on both midaxillary lines. Anisotropic volumetric atrial flutter simulations have been used for validation.